Investigating the links between diagnostic uncertainty, emotional exhaustion, and turnover intention in General Practitioners working in the United Kingdom - Zhou, Anli Yue; Zghebi, Salwa S.; Hodkinson, Alexander; Hann, Mark; Grigoroglou, Christos; Ashcroft, Darren M.; Esmail, Aneez; Chew-Graham, Carolyn A.; Payne, Rupert; Little, Paul; Lusignan, Simon de; Cherachi-Sohi, Sudeh; et al. (Frontiers in Psychiatry, 2022)
Background: General practitioners (GPs) report high levels of burnout, job dissatisfaction and turnover intention. The complexity of presenting problems to general practice makes diagnostic uncertainty a common occurrence that has been linked to burnout. The interrelationship between diagnostic uncertainty with other factors such as burnout, job satisfaction and turnover intention have not been previously examined. Objectives: To examine associations between diagnostic uncertainty, emotional exhaustion (EE), depersonalisation (DP), job satisfaction and turnover intention in GPs. Methods: Seventy general practices in England were randomly selected through the Oxford-Royal College of General Practitioners Research and Surveillance Centre (RCGP-RSC). A total of 348 GPs within 67 these practices completed a 10-item online questionnaire which included questions on GP characteristics, work-life balance, job satisfaction, sickness presenteeism, diagnostic uncertainty, turnover intention as well as EE and DP. Associations between diagnostic uncertainty and each of EE, DP, job satisfaction and turnover intention were evaluated in multivariate mixed-effect ordinal logistic regressions whilst adjusting for covariates, to account for the correlation in the three outcomes of interest. Results: Almost one-third of GPs (n=101; 29%) reported experiencing >10% of diagnostic uncertainty in their day-to-day practice over the past year. GPs reporting greater diagnostic uncertainty had higher levels of EE [OR=3.90;95%CI=(2.54,5.99)], job dissatisfaction [OR=2.01;95%CI=(1.30,3.13)] and turnover intention [OR=4.51;95%CI=(2.86,7.11)]. GPs with no sickness presenteeism had lower levels of EE [OR=0.53;95%CI=(0.35,0.82)], job dissatisfaction [OR=0.56;95%CI=(0.35,0.88)], and turnover intention [OR=0.61;95%CI=(0.41,0.91)]. Conclusions: Diagnostic uncertainty may not only negatively impact on the wellbeing of GPs, but could also have adverse implications on workforce retention in primary care.